Feelings experienced by parents when their premature children are hospitalized. A contribution to the humanized care - Acosta Romo, Maria Fernanda; Cabrera Bravo, Nancy; Basante Castro, Yudy del Rosario; Jurado, Daniel Marcelo (Universidad y Salud, 2017)
Objective: To understand the meaning of the experiences felt by parents of premature children who are hospitalized in the Neonatal Intensive Care Unit of a hospital in the city of Pasto, Nariño, taking into account the phenomenological theory of Edmund Husserl. Materials and methods: In order to understand these experiences, a qualitative phenomenological study was carried out with eight parents in a range of age between 17 and 35. Results: The investigative process identified five categories, which emerged from the process of codification or nomothetic analysis of the speeches convergences. Two of these categories were considered for this article: Feelings and affective bond as an expression of parental love and process of interaction with the health staff. Conclusion: The parents of children in hospital were not prepared for the birth of a premature baby, so they experienced feelings of sadness, anxiety, self-criticism and fear, altering the affective bond between parents and children.